2011
DOI: 10.1007/s00167-011-1615-9
|View full text |Cite
|
Sign up to set email alerts
|

An anatomical three-dimensional study of the posteromedial corner of the knee

Abstract: Posteromedial corner ligament structures are quite complex and are not always clearly described in the literature. Three-dimensional images of these structures can help better understanding its anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…The PMC is an additional stabilizer, providing one-third of the restraint to valgus stress when the knee is in extension. After isolated MCL injury, the POL acts as an important secondary stabilizer for rotation and valgus stress (14,(19)(20)(21)24,(26)(27)(28).…”
Section: Biomechanics and Function Of The Pmcmentioning
confidence: 99%
“…The PMC is an additional stabilizer, providing one-third of the restraint to valgus stress when the knee is in extension. After isolated MCL injury, the POL acts as an important secondary stabilizer for rotation and valgus stress (14,(19)(20)(21)24,(26)(27)(28).…”
Section: Biomechanics and Function Of The Pmcmentioning
confidence: 99%
“…11 12 A inserção tibial distal situa-se entre 46 e 60 mm distal à articulação, 13 sendo seu comprimento total de 90 a 110 mm. 5 14 Em sua inserção tibial distal, as fibras misturam-se tangencialmente com o periósteo. 15 16 O LCMs apresentou-se, no presente estudo, com uma média de 11,35 mm de largura em sua inserção femoral, apresentando em sua inserção tibial distal uma largura média de 12,30 mm, com fibras conectadas à pata de ganso.…”
Section: Discussionunclassified
“…11 12 The distal tibial insertion is between 46 and 60 mm distal to the joint, 13 of which its total length is 90 to 110 mm. 5 14 In its distal tibial insertion, the fibers mix tangentially with the periosteum. 15 16 The MCLs presented, in the present study, with an average width of 11.35 mm in its femoral insertion, presenting in its distal tibial insertion an average width of 12.30 mm, with fibers connected to the pes anserinus.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment may cause knee function limitation and accelerate the development of osteoarthritis 15 . Previous clinical studies have found that only repairing MCL without repairing POL cannot completely restore the static stability of the knee joint 2,16 , since, with a separate MCL damage, POL has become an important stable structure for controlling the rotation and valgus stress in the knee 5,17,18 .…”
Section: Discussionmentioning
confidence: 99%